Relationship of breastfeeding duration with joint pain and knee osteoarthritis in middle-aged Korean women: a cross-sectional study using the Korea National Health and Nutrition Examination Survey - Min-Young Kim; Hyun-Joong Kim; Je-Heon Noh; Sun-A Kim; Deok-Sang Hwang; Chang-Hoon Lee; In-Hyuk Ha (BMC, 2020)
Abstract Background The effect of joint health on the quality of life of middle-aged and older women is becoming more widely recognized with the aging of the world's population. However, the association of long-term breastfeeding with joint pain and knee osteoarthritis has not been fully examined. The aim of this study was to determine the association of prior breastfeeding duration with current joint pain and knee osteoarthritis in middle-aged Korean women. Methods This cross-sectional study was conducted among 3454 women aged ≥50 years who underwent knee radiography and answered a questionnaire on breastfeeding and joint pain for the 5th Korea National Health and Nutrition Examination Survey (2010-2011). After adjusting for confounding sociodemographic, medical history, and obstetric and gynecologic variables, logistic regression analysis was conducted to analyze the prevalence of joint pain and knee osteoarthritis according to breastfeeding and its duration. Results Among the 3454 participants, 298 had not breastfed and 1042, 815, and 1299 had breastfed for 1-24, 25-48, and ≥ 49 months, respectively. Of all participants, 1731 had joint pain and 739 were diagnosed with knee osteoarthritis after radiography. Using the non-breastfeeding group as a reference, the odds ratio (OR) for joint pain among women who breastfed ≥1 month was 1.49 (95% confidence interval [CI] 1.01-2.21). As the breastfeeding duration increased, the OR of joint pain prevalence also increased (p for trend; p = 0.002). For knee osteoarthritis, the OR was 2.30 in the 25-48 months group (95% CI 1.09-4.86). The OR of knee osteoarthritis in the ≥49 months group was 2.17 (95% CI 1.01-4.64). Sensitivity analysis after selecting only participants aged ≥60 years showed that the prevalence of joint pain and knee osteoarthritis was more positively correlated with extended breastfeeding duration (joint pain, p for trend; p = 0.005) (knee osteoarthritis, p for trend; p = 0.012). Conclusions Long-term feeding for more than 25 months was associated with an increased prevalence of joint pain and degenerative arthritis in Korean women aged ≥50 years.